Biological treatment of DMSO-containing wastewater from semiconductor industry under aerobic and methanogenic conditions. (December 2019) - Cheng, Hai-Hsuan; Liu, Cheng-Bing; Lei, Yuan-Yuan; Chiu, Yi-Chu; Mangalindan, Jasan; Wu, Chin-Hwa; Wu, Yi-Ju; Whang, Liang-Ming
Abstract: This study evaluated biological treatment of dimethyl sulfoxide (DMSO)-containing wastewater from semiconductor industry under aerobic and anaerobic conditions. DMSO concentration as higher as 1.5 g/L did not inhibit DMSO degradation efficiency in aerobic membrane bioreactor (MBR), while specific DMSO degradation rate at different initial DMSO-to-biomass (S0 /X0 ) ratios from batch tests seemed to follow the Haldane-type kinetics. According to the microbial community analysis, Proteobacteria decreased from 88.2% to 26% as influent DMSO concentration increased, while Bacteroidetes, Parcubacteria, Saccharibacteria increased. Within the Bacteroidetes class, Flavobacterium and Laribacter genus significantly increased from less than 0.05%–26.8% and 13.4%, respectively, which might both be related to the DMS degradation. Hyphomicrobium and Thiobacillus, known as aerobic DMSO and DMS degraders, instead, decreased at higher DMSO conditions. Under methanogenic conditions, batch results implied DMSO concentrations higher than 3 g/L could be inhibitory, while DMSO and COD removal achieved 100% and 93%, respectively, using a pilot-scale anaerobic fluidized bed membrane bioreactor (AFMBR) with influent DMSO below 1.5 g/L. Results of terminal restriction fragment length polymorphism (TRFLP) analysis targeting on mcr A functional gene revealed that Methanomethylovorans sp. was dominant in AFMBR after 54 days of operation, indicating its importance on degrading DMS and mathanethiol (MT). Highlights: Both aerobic and methanogenic bioreactors can remove DMSO at loading of 1.5 and 0.3 kg/m 3 /d. Higher DMSO loading presents Haldane-type inhibitory effects on aerobic degradation. DMS accumulation observed during methanogenic degradation. DMS-degrading microorganisms are important when treating DMSO-containing wastewater.